What are the contemporary sources of sediment in the Mississippi River?. Issue 17 (9th September 2017) - Hassan, M. A.; Roberge, L.; Church, M.; More, M.; Donner, S. D.; Leach, J.; Ali, K. F.
Abstract: Within the last two centuries, the Mississippi River basin has been transformed by changes in land use practices, dam construction, and training of the rivers for navigation. Here we analyze the contemporary patterns of fluvial sediment yield in the Mississippi River basin using all available data in order to assess the influence of regional land condition on the variation of sediment yield within the basin. We develop regional‐scale relations between specific sediment yield (yield per unit area) and drainage area to reveal contemporary regional sediment yield patterns and source areas of riverine sediments. Extensive upland erosion before the development of soil conservation practices exported large amounts of sediment to the valleys and floodplains. We show that sediment today is sourced primarily along the river valleys from arable land, and from stream bank and channel erosion, with sediment yields from areas dominated by arable land 2 orders of magnitude greater than that of grassland dominated areas. Comparison with the " T factor, " a commonly quoted measure of agricultural soil resilience suggests that the latter may not reflect contemporary soil loss from the landscape. Key Points: We use an unexploited data set to study spatial patterns of sediment dynamics along the Mississippi basin Our analysis shows that river sediments today are derived primarily from the major valleys The results have implication toward soil security and management